Vascular Growth in Health and Disease - Bondke Persson, Anja; Buschmann, Ivo R. (Frontiers in Molecular Neuroscience, 2011)
Vascular growth forms the first functional organ system during development, and continues into adult life, wherein it is often associated with disease states. Genetically determined vasculogenesis produces a primary vascular plexus in ontogenesis. Angiogenesis, occuring e.g. in response to metabolic stress within hypoxic tissues, enhances tissue capillarization. Arteriogenesis denotes the adaptive outgrowth of preexistent collateral arteries to bypass arterial stenoses in response to hemodynamic changes. It has been debated whether vasculogenesis occurs in the adult, and whether or not circulating progenitor cells structurally contribute to vessel regeneration. Secondly, the major determinants of vascular growth - genetic predisposition, metabolic factors (hypoxia) and hemodynamics - cannot be assigned in a mutually exclusive fashion to vasculogenesis, angiogenesis and arteriogenesis, respectively; rather, mechanisms overlap. Lastly, all three mechanisms of vessel growth seem to contribute to physiological embryogenesis as well as adult adaptive vascularization as occurs in tumors or to circumvent arterial stenosis. Thus, much conceptual and terminological confusion has been created, while therapies targetting neovascularization have yielded promising results in the lab, but failed randomised studies when taken to the bedside. Therefore, this review article aims at providing an exact definition of the mechanisms of vascular growth and their contribution to embryonic development as well as adult adaptive revascularization. We have been looking for potential reasons for why clinical trials have failed, how vitally the application of appropriate methods of measuring and assessment influences study outcomes, and how relevant e.g. results gained in models of vascular occlusive disease may be for antineoplastic startegies, advocating a reverse bedside-to-bench approach, which may hopefully yield successful approaches to therapeutically targetting vascular growth.